Analisis Penerapan Manajemen Dokumentasi Asuhan Keperawatan Elektronik - Solehudin Solehudin; Sancka Stella; Firyal Firyal; Nur Eni Lestari; Yeni Koto; Hari Ghanesia Istiani; Bambang Suryadi; Saiful Gunardi; Agus Purnama; Susaldi Susaldi; Weslei Daeli; Arif Hidayatullah (JURNAL RISET RUMPUN ILMU KESEHATAN, 2024)
Electronic nursing care documentation plays an important role in maintaining patient safety. Electronic documentation can identify the potential for increasing efficiency and effectiveness in providing nursing care. The purpose of this article is to determine the application of electronic nursing care documentation management. This research is a case study obtained when students carried out the Nursing Management Stage practice at one of the hospitals in Bogor City from 16 October - 10 November 2023. Data collection was carried out through several processes which included management review of electronic documentation based on 5M, SWOT analysis and formulation and problem priorities using the criteria of magnitude, severity, manageability, nursing concern, affordability which are assessed with a score of 1 – 5. The vision of room X is electronic-based so that effective nurses need time to adapt to technology to carry out electronic-based nursing documentation. The conclusion is that documentation of nursing care plays a crucial role as an important process for recording patient care information.